Is Depression After Childbirth Correlated by The Number of Children in The Family? - Lita Nafratilova; Wan Anita (STIKes Patria Husada Blitar, 2024)
The postpartum blues are frequently disregarded, which makes early diagnosis difficult. As a result, postpartum mothers are more likely to develop emotional disorders, which may affect their ability to be good mothers. The aim of this research was to find out whether there was a relationship between the number of children and the incidence of postpartum blues. With a cross sectional design, this research was analytical in nature. The sample of this research was parts of postpartum women with purposive sampling. at the Ernita Midwife Independent Practice based on the inclusion criteria, which had 35 respondents. The results of the examination of the connection between parity and postpartum depression showed a strong correlation between the two, with a p value of 0.002 (p = 0.05) for postpartum maternal parity. Families should consider the number of children, especially toddlers, while planning their next pregnancy, suggests the researcher